Oromandibular Dystonia: Clinical and Demographic Data from Eight-Two Patients - Balal, Mehmet; Demirkiran, Meltem (Tremor and other hyperkinetic movements (New York, N.Y.), 2023)
This study aimed to determine the demographic and clinical characteristics of patients with oromandibular dystonia (OMD). Dystonia is a movement disorder characterized by sustained involuntary muscle contractions that often cause abnormal postures. OMD is a rare focal dystonia that affects the tongue, jaw, and mouth. OMD, which is a rare public health problem, is often recognized as psychogenic and there are delays in its diagnosis and treatment. Patients with OMD, both isolated and combined, followed at our Movement Disorders Outpatient Clinic between 2004 and 2021 were enrolled in this study. Age, sex, age at onset, and disease duration were recorded. The type of OMD, affected muscles, etiologies of accompanying neurological disorders, and treatment were noted. A total of 82 patients (44 women, 38 men) were included in this study. Among these, 39 patients had isolated OMD, and 43 patients had either segmental or generalized dystonia. Seven patients reported a family history of dystonia. Only nine patients reported a sensory trick. The average disease duration was 6.01 ± 3.73 (range, 1-29) years, and the average age at onset was 43.34 ± 18.24 (range, 1-78) years. The disease etiology was unknown (idiopathic) in most patients. Fifteen patients reported task-specific dystonia. The most common type of dystonia was jaw-opening dystonia. OMD is focal dystonia that significantly affects the quality of life. This study adds more data to the literature by defining the clinical features of this rare disorder and draws attention to this neglected type of dystonia.